Cereblon modulator iberdomide induces degradation of the transcription factors Ikaros and Aiolos: immunomodulation in healthy volunteers and relevance to systemic lupus erythematosus. Issue 10 (26th June 2018) - Schafer, Peter H; Ye, Ying; Wu, Lei; Kosek, Jolanta; Ringheim, Garth; Yang, Zhihong; Liu, Liangang; Thomas, Michael; Palmisano, Maria; Chopra, Rajesh
Abstract : Objectives: IKZF1 and IKZF3 ( encoding transcription factors Ikaros and Aiolos) are susceptibility loci for systemic lupus erythematosus (SLE). The pharmacology of iberdomide (CC-220), a cereblon ( CRBN ) modulator targeting Ikaros and Aiolos, was studied in SLE patient cells and in a phase 1 healthy volunteer study. Methods: CRBN, IKZF1 and IKZF3 gene expression was measured in peripheral blood mononuclear cells (PBMC) from patients with SLE and healthy volunteers. Ikaros and Aiolos protein levels were measured by Western blot and flow cytometry. Anti-dsDNA and anti-phospholipid autoantibodies were measured in SLE PBMC cultures treated for 7 days with iberdomide. Fifty-six healthy volunteers were randomised to a single dose of iberdomide (0.03–6 mg, n=6 across seven cohorts) or placebo (n=2/cohort). CD19+ B cells, CD3+ T cells and intracellular Aiolos were measured by flow cytometry. Interleukin (IL)-2 and IL-1β production was stimulated with anti-CD3 and lipopolysaccharide, respectively, in an ex vivo whole blood assay. Results: SLE patient PBMCs expressed significantly higher CRBN (1.5-fold), IKZF1 (2.1-fold) and IKZF3 (4.1-fold) mRNA levels compared with healthy volunteers. Iberdomide significantly reduced Ikaros and Aiolos protein levels in B cells, T cells and monocytes. In SLE PBMC cultures, iberdomide inhibited anti-dsDNA and anti-phospholipid autoantibody production (IC50 ≈10 nM). Single doses of iberdomide (0.3–6 mg) in healthy volunteers decreased intracellular Aiolos (minimum mean per cent of baseline: ≈12%–28% (B cells); ≈0%–33% (T cells)), decreased absolute CD19+ B cells, increased IL-2 and decreased IL-1β production ex vivo. Conclusions: These findings demonstrate pharmacodynamic activity of iberdomide and support its further clinical development for the treatment of SLE. Trial registration number: NCT01733875 ; Results.